EDUCAÇÃO COLONIAL EM PERNAMBUCO: UM ESTUDO DE CASO - Luiz Gustavo Lima Freire (Associação Sul-Rio-Grandense de Pesquisadores em História da Educação (ASPHE), 2011)
This article aims to reflect on the colonial education, specifically during the eighteenth century, held in Brazil in the province of Pernambuco. To meet this objective we will use some documents from "Arquivo Histórico Ultramarino" looking for to understand how they can representing the ideas that prevailed during that period. It is intended that context, to understand what were the proposed guidelines for teaching in some indian villages in Pernambuco and how were consistent with the policy of the marquis of Pombal and the foundations of the Enlightenment.